New records of cascade frogs of the genus Odorrana (Amphibia: Anura: Ranidae) from Vietnam - Cuong, Pham The; Minh, Le Duc; Hanh, Ngo Thi; Truong, Nguyen Quang (Academia Journal of Biology, 2020)
Odorrana fengkaiensis was recorded for the first time from Vietnam based on a new amphibian collection from Cao Bang, Bac Kan, Bac Giang, Quang Ninh provinces. Sequences of the specimens from Vietnam were identical to those of the paratypes of O. fengkaiensis from China. In addition, O. trankieni was newly recorded from Hoa Binh and Bac Giang provinces, Northern Vietnam, including the first description of female individuals. Genetic divergence between O. trankieni from Vietnam and its sister species, O. nasuta from China, ranged from 1.42 to 2.66%. The intra-specific genetic distance within O. trankieni ranged from 0.68 to 1.88% between the northeastern and northwestern populations.